2016
DOI: 10.1016/j.seizure.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Polytherapy with sodium channel-blocking antiepileptic drugs is associated with arrhythmogenic ST-T abnormality in patients with epilepsy

Abstract: ST-T abnormalities were frequently seen in patients using AEDs. The presence of Brugada-type ST elevation was associated with polytherapy with sodium channel-blocking AEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
0
26
1
3
Order By: Relevance
“…Atrioventricular (AV) conduction is the most frequent reported complication. ST changes, Brugada-like patterns, atrial fibrillation and QTc prolongation have also been reported but the association with AED treatment is less well established [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Most clinically relevant arrhythmias were related to AED overdose.…”
Section: Epilepsy and Cardiac Arrhythmiasmentioning
confidence: 99%
“…Atrioventricular (AV) conduction is the most frequent reported complication. ST changes, Brugada-like patterns, atrial fibrillation and QTc prolongation have also been reported but the association with AED treatment is less well established [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Most clinically relevant arrhythmias were related to AED overdose.…”
Section: Epilepsy and Cardiac Arrhythmiasmentioning
confidence: 99%
“…An abnormal ECG was recorded in 1 patient in the monotherapy subgroup and in 10 patients in the polytherapy subgroup (p = 0.05). As reported in the literature, polytherapy increases the risk of arrhythmia [7].…”
mentioning
confidence: 79%
“…However, an abnormal ECG trace requires the exclusion of heart disease and verification of the diagnosis of epilepsy. ECG changes could also be explained by the influence of epileptic discharges on the central autonomic nervous system, the effect of antiepileptic drugs (AEDs) and the presence of genetically determined disorders of ion channel function [1][2][3][4][5][6][7]. Detection of ECG changes is also important because of the phenomenon of sudden unexpected death in epilepsy (SUDEP) [2].…”
mentioning
confidence: 99%
“…It appears, however, plausible that simultaneous administration of AEDs that bind to the same cellular targets increases the risk of target-related side effects. Therefore, it is not surprising that cardiac side effects such as atrioventricular block, sinus node dysfunction, or arrhythmogenic ST–T abnormalities were reported in the context of simultaneous intake of AED that inhibits VGSC (3436). We think that cardiac side effects can indeed, if long lasting and severe enough, facilitate sudden cardiac death as a rare cause of SUDEP in some epilepsy patients.…”
Section: Discussionmentioning
confidence: 99%